Directional Spreading Model in a Wave Channel. Wave Propagation and Wave Breaking - Neves, D. R. (2012)
The presented work describes a wide range of wave channel tests performed at the National Laboratory of Civil Engineering (LNEC) with the main objective of introducing an extensive wave analysis regarding mainly the directional spreading analysis of the wave propagation under conditions of wave breaking on complex bathymetries. Therefore, this paper shows the experimental setup, the incident wave conditions, the measurements (free surface elevation and particle velocity) along the wave channel, especially at the wave breaking zone. Based upon the time series of the wave data measurements, a time, spectral and statistical analysis was performed and presented. Analyses are presented relating to: (i) the relative wave height (H/d); (ii) the wave celerity; (iii) the two-dimensional distribution of the particle velocities components; finally (iv) the average wave direction and spreading angle were carried out. The directional spreading analysis was supported by all the other calculated quantities in order to have an effective analysis on the wave breaking phenomena. The work performed contributed for a better understanding of the wave breaking process and especially at the end part of it. Moreover, the data obtained and the results of the performed analysis constitute an important basis for the establishment/improvement of numerical wave breaking models and its validation.